Territoriale Grenzen als Praxis Zur Erfindung der Grenzregion in grenzüberschreitender Kartografie - Connor, Ulla (Border Studies. Cultures, Spaces, Orders, 2023)
In this study, the author develops practice orientation in border studies and shows how borders can be understood and researched as a form of social practice. Using a praxeological approach at the intersection of sociology and border studies, the author paves the way for complex border practices in cross-border coop-eration. Her ethnography of cross-border mapping provides a dense description of the daily office work of administrators and allows us to understand how border regions are formed. This book makes a theoretical and conceptual contribution to the young field of praxeological border research. Ulla Connor explores border regions from a sociological perspective.